Iron oxide nanoparticles empowering melanoma therapy: advances in multifunctional platform research - Bai, Xiaolong; Wang, Zhijun; Cao, Ziyi; Zhen, Junping (Frontiers in Bioengineering and Biotechnology, 2025)
Melanoma, one of the most aggressive types of skin cancer, has exhibited a continuously rising incidence worldwide, accompanied by a significant mortality risk. Despite ongoing advances in therapeutic approaches, effective and definitive clinical interventions remain limited, severely restricting long-term patient prognosis. In recent years, nanotechnology-based tumor therapies have demonstrated tremendous potential. Among them, iron oxide nanoparticles (IONPs), owing to their excellent biocompatibility, magnetic responsiveness, low cost, and scalability in synthesis, have emerged as a highly promising nanoplatform for melanoma treatment. This review systematically summarizes the physicochemical properties of IONPs and their tumor-targeting mechanisms, with a particular focus on recent advances in their applications for melanoma, including drug-targeted delivery, hyperthermia, Photodynamic therapy (PDT), Chemodynamic therapy (CDT), immunotherapy, and combination therapies. Additionally, the review discusses current challenges and provides perspectives on the future development of IONPs for precision melanoma therapy.